Implementation of Marriage Law no. 16 of 2019 in Preventing Early Marriage in Subang District - Sri Nurcahyani (IHSA Institute, 2021)
The age limit of marriage according to Law number 1 of 1974 provides space for anyone to marry underage, this is a dynamic for Indonesia, especially Subang Regency with the highest number of underage marriages and high divorce and domestic violence (KDRT), therefore research This aims to see how the implementation of the Marriage Law No. 16 of 2019 prevents early childhood marriages in Subang Regency. This study uses a qualitative approach with empirical study methods. Data collection is carried out by facts in society. The results showed that the implementation of the Marriage Law requires support from related stakeholders, the central government,